2011
DOI: 10.1038/nnano.2011.146
|View full text |Cite
|
Sign up to set email alerts
|

Graphene plasmonics for tunable terahertz metamaterials

Abstract: Plasmons describe collective oscillations of electrons. They have a fundamental role in the dynamic responses of electron systems and form the basis of research into optical metamaterials. Plasmons of two-dimensional massless electrons, as present in graphene, show unusual behaviour that enables new tunable plasmonic metamaterials and, potentially, optoelectronic applications in the terahertz frequency range. Here we explore plasmon excitations in engineered graphene micro-ribbon arrays. We demonstrate that gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

57
2,286
4
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,755 publications
(2,362 citation statements)
references
References 28 publications
57
2,286
4
15
Order By: Relevance
“…Second, intraband transitions dominate in the terahertz range, resulting in an optical conductivity well described by the Drude model. Plasmonic effects in graphene were also recently observed 7 , which are important in the transition range from terahertz to infrared. Rooted in these understandings, several devices based on interband transitions have been demonstrated, including transparent electrodes 10 , photodetectors 11 , and broadband infrared electro-optical modulators 12 .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Second, intraband transitions dominate in the terahertz range, resulting in an optical conductivity well described by the Drude model. Plasmonic effects in graphene were also recently observed 7 , which are important in the transition range from terahertz to infrared. Rooted in these understandings, several devices based on interband transitions have been demonstrated, including transparent electrodes 10 , photodetectors 11 , and broadband infrared electro-optical modulators 12 .…”
mentioning
confidence: 74%
“…On the basis of their peculiar band structures, single-layer graphene and Bernal-stacked bilayer graphene have been proposed for novel terahertz [3][4][5][6][7] and optoelectronic devices 8 , with some successful experimental demonstrations [9][10][11][12] . Interband and intraband transitions under optical excitation in graphene have been investigated by various groups [13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…To fabricate next generation electronic devices incorporating graphene, it is pertinent to develop a variety of methods for direct synthesis of graphene on any substrate. However, various methods have been adopted for controlled growth of graphene, and it was found that direct growth of graphene especially on dielectrics is difficult to achieve due to their low surface energy 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. However, the surface modification of dielectric substrates can facilitate the ease of nucleation of graphene 10, 12.…”
Section: Introductionmentioning
confidence: 99%
“…While the plasmonic response of metals is weak at the infrared or lower frequencies, graphene plasmons exist in the THz regime with relatively low losses. [13][14][15] These facts, added to the important ingredient of tunability, make graphene a very suitable platform for the design of plasmonic metasurfaces in the THz regime. 16,17 Metasurfaces, the 2D counterpart of metamaterials, 18,19 consist of a planar arrangement of resonant subwavelength-sized building blocks.…”
mentioning
confidence: 99%